Motives and barriers to the implementation of renewable energy sources in South African tertiary institutions - Sibindi, Siyangiso (Rhodes University, Faculty of Commerce, Rhodes Business School)
Organisations face major challenges to address the exploitation of non-renewable resources and consider management considerations for dealing with climate change. Organisations have been pushed to play a part in their carbon footprints and in curbing climate change. Among these organisations are tertiary institutions that can greatly impact environmental sustainability and address carbon dioxide emissions by embarking on renewable energy technologies. Tertiary institutions play a major role in society by the provision of skilled labour and personnel that are equipped to deal with a range of advancements and challenges. The sustainability of these tertiary institutions has thus been called into question due to the impact they can bring to societies. This research thus aims to identify the motives and barriers to renewable energy adoption in tertiary education institutions. To do this, a literature review was conducted to identify possible motives and barriers to renewable energy adoption. These were then compiled into a questionnaire that was sent to respondents of three different institutions. Respondents were then requested to give feedback on each of the motives and barriers. The respondents were also asked general questions found in literature that addressed the adoption of renewable energy technologies in tertiary institutions. The data was collected using the designed questionnaires. The respondents were able to articulate their perceived barriers and motives to the implementation of renewable energy technologies in tertiary institutions. Data analysis was done using thematic analysis. The results showed that the barriers in the implementation of renewable energy technologies in tertiary institutions were: 'Cost to Install', 'Transition Process' and 'Government Policies'. The motives on why educational institutions need to embark on renewable energy projects were found to be 'Energy Independence', 'Cleaner Source of Energy' and 'Reduction in Carbon Emissions'. The cost of renewable energy technologies, the process of moving from the Eskom grid, and renewable energy policies that are ambiguous were some factors that were highlighted by respondents on why it is challenging to adopt renewable energies in tertiary institutions. On the other hand, the effects of load shedding currently being experienced in the country and the migration to cleaner sources of energy that cause less harm to the environment, are some of the drivers noted by respondents on why tertiary institutions need to embark on renewable energy technologies. More emphasis needs to be put by stakeholders on tertiary institutions to migrate to cleaner sources of energy, and policies need to be put in place in order to promote institutions to adopt these types of energies. Governments and other role-players need to be visible at all times in addressing energy challenges in tertiary institutions in the wake of the recent load-shedding concerns that have been crippling South Africa.
Keywords: Renewable energy sources -- South Africa; Education, Higher -- South Africa; Education, Higher Environmental aspects -- South Africa; Environmental responsibility -- South Africa; Climate change mitigation -- South Africa; Sustainable development -- South Africa